The Effectiveness of Mindfulness-Based Cognitive Therapy on Marital Relationship Quality and Forgiveness in Women in Second Marriages - Gholipor, Forozan; Rezaei, Fatemezahra; Mazlomi, Maryam; Hamlehvarsheikhrajeh, Fateme; Babazadeh, Jalal (Psychology of Woman Journal, 2025)
Objective: The present study aimed to determine the effectiveness of mindfulness-based cognitive therapy on marital relationship quality and forgiveness in women in second marriages. Methods and Materials: The research method was quasi-experimental with a control and experimental group design. The statistical population consisted of women in second marriages who attended counseling centers in Babol city in 2022. Using convenience sampling, 30 individuals were selected as the sample size and randomly assigned into two groups: experimental (15 individuals) and control (15 individuals). Data collection was conducted using the Marital Relationship Quality and Forgiveness questionnaires. Initially, a pre-test was administered to both groups (experimental and control) using the aforementioned questionnaires. Subsequently, the experimental group received eight 90-minute sessions of mindfulness-based cognitive therapy, while the control group received no intervention. Findings: The findings indicated that in the experimental group, the post-test scores showed an improvement in the mean marital relationship quality and forgiveness compared to the pre-test scores. Conclusion: Therefore, mindfulness-based cognitive therapy impacts marital relationship quality and forgiveness in women in second marriages.